THE ROLE OF COMPUTERIZED PLANNING IN MODERN IMPLANT-PROSTHETIC THERAPY - Forna Norina; Creţu Cosmin; Topoliceanu Claudiu; Ţarevici Eugenia Larisa; Ţibeica Silviu Catalin; Ursu Marius Octavian; Agop-Forna Doriana (Romanian Dental Association for Education, 2020)
The optimization of the implant-prosthetic rehabilitation of the patients, with the help of computerized systems, aims at restoring the functions of the stomatognathic system and improving the quality of life. The combined use of clinical, paraclinical and computerized examination allows the planning of specific pro-prosthetic and pro-implant interventions at the level of dento-periodontal and muco-osseous support to correct negative clinical-biological indications, and to optimize the biomechanics of implant-prosthetic restorations. the use of the tools of digital assessment combined with classic techniques will allow the dental practitioners to create virtual, ideal restorations and to manage implant positions based on simplified, cost-effective techniques. Pre- and pro-prosthetic computer planning also plays an important role in reducing the risk of accidents in dental medical practice.